Astrobiology and Christian Doctrine: Disputatio Rediviva - Arnould, Jacques (Theology and science, 2024)
In his book Astrobiology and Christian Doctrine, Andrew Davison conducts an in-depth study of the implications of the search for life in the universe for the main themes of Christian theology, and develops new perspectives on them, particularly in the field of Christology. His reflections on eschatology lead me to introduce the vision developed by Pierre Teilhard de Chardin, based on faith in the cosmic Christ.